Application of nanobiosensors for diagnostics of the acute coronary syndrome in emergency medicine - Adam A. Khasanov (Computational nanotechnology, 2026)
The primary and mandatory tool for the diagnosis of ACS is an electrocardiogram. However, ECG can reliably distinguish only one type of ACS, namely myocardial infarction with ST-segment elevation. MI without ST-segment elevation cannot be detected with aid of ECG but modern medicine employs such instruments as cardiobiomarkers’ concentration measurement in human blood for this. Due to the relatively low, in the range of nanograms per liter, concentrations of biomarkers, such as Troponin I and Troponin T, miniaturized and highly sensitive instruments are needed. With the development of nanotechnology, nanobiosensors are becoming available allowing for the conduction of such research. The present analysis introduces some of the types of nanobiosensors capable of measuring these biomarkers with the required sensitivity and accuracy in human blood plasma.